Mystics. By William Harmless, SJ - Lane, Margaret (The journal of theological studies, 2010)
In this excellent and very readable introduction to the mystics, the author has adopted a case-study approach to the subject instead of the usual historical or systematic approaches (though he does draw on these to some extent). His approach is reminiscent of the one adopted by William James in his famous Varieties of Religious Experience, though it is crucially and deliberately different. For the underlying argument of the author is that James’s pared down psychological approach is only an element of the truth of mysticism.